1998
DOI: 10.1300/j145v01n04_05
|View full text |Cite
|
Sign up to set email alerts
|

On Individual Difference, Choice, Selection, and Complexity in Adoption Research

Abstract: The silent confounds of the Main Effects Model as used in adoption research are individual difference driven self-selection and choice along with intermediary and birthparent selections. Two Chain-of-Choices Models--one for adoptive parents and one for birthparents and adoptees--are presented as possible frameworks within which to consider the role of individual differences, choices, and selections in understanding both the process of adoption and adoption outcomes. The article concludes with an extensive disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 3 publications
2
7
0
Order By: Relevance
“…When adoptive fathers are more involved in adolescents' development, this can generate positive dynamics in adoptive families, which can reduce adolescents' school failure and course failure. The findings also agree with the social role theory that adoptive fathers are their children's only father figures (Finley, 1998;Troilo & Coleman, 2008); these fathers make firm commitments to the children from the beginning, which is different from stepfathers or nonresident biological fathers. These findings about adoptive fathers are important in light of Kriebel and Wentzel's (2011) findings that children with risk factors prior to adoption are at risk for poorer outcomes without parental investment and warmth.…”
Section: Adolescents With Resident Fatherssupporting
confidence: 85%
See 1 more Smart Citation
“…When adoptive fathers are more involved in adolescents' development, this can generate positive dynamics in adoptive families, which can reduce adolescents' school failure and course failure. The findings also agree with the social role theory that adoptive fathers are their children's only father figures (Finley, 1998;Troilo & Coleman, 2008); these fathers make firm commitments to the children from the beginning, which is different from stepfathers or nonresident biological fathers. These findings about adoptive fathers are important in light of Kriebel and Wentzel's (2011) findings that children with risk factors prior to adoption are at risk for poorer outcomes without parental investment and warmth.…”
Section: Adolescents With Resident Fatherssupporting
confidence: 85%
“…Interestingly, although overall performance for adolescents with adoptive fathers was lower than for those who lived with their biological families, the regression analysis indicated that there was not a significant difference from those with biological fathers in school or course performance. Adoptive fathers tend to have more commitment to their children because of comparatively high role clarity (Finley, 1998). These findings are consistent with the stereotype of adoptive fathers, who are perceived to be more compassionate, giving, supportive, and well meaning when compared to divorced, nonresidential, and never-married fathers (Troilo & Coleman, 2008).…”
Section: Adolescents With Resident Fatherssupporting
confidence: 75%
“…Is it possible that the experience of coping with birth parent loss will help to buffer or protect against the adoptive parent loss? Is it further possible that adoptee individual differences may play a role in tilting the balance towards either risk or protective functions (Finley, 1998)? Many in the adoption community likely would share the position well articulated by Brodzinsky, Hitt and Smith (1993) in the introduction to their study.…”
Section: Adoptive Family Divorce: a New Perspective On Adoptee Risk Amentioning
confidence: 99%
“…Indeed, such differences in research methods have been postulated as potentially leading to different findings with respect to adoptee outcome (Park & Green, 2000;Courtney, 1997). Accordingly, some researchers contend that determining whether or not adoption in general is a risk factor is less meaningful than identifying the specific conditions that are associated with maladjustment for adoptee development (Brodzinsky, Smith, & Brodzinsky, 1998;Finley, 1998 adolescents. This is one of the most consistent patterns in the present results.…”
Section: Synthesis Of Literature Review and Resultsmentioning
confidence: 99%
“…(Finley, 1999c). To rationalize the purported inconsistencies, some scholars assert that methodological shortcomings have diluted the adoption literature (Brodzinsky, 1993;Finley, 1998;Finley, 1999c). Small sample sizes, sampling biases, insufficient comparison groups, and inadequate measures of adjustment are commonly cited as problems within adoption studies, making conclusions less generalizable (Park & Green, 2000;Courtney, 1997).…”
Section: Adoptee Versus Non-adoptee Empirical Researchmentioning
confidence: 99%